Between Assimilation and Identity: The Dynamics of the Jewish Community in Indonesia - Irwansyah Irwansyah; Mukhlis Lubis (Pelopor Publikasi Akademika, 2024)
This research examines the existence and dynamics of the Jewish community in Indonesia, which has deep historical roots dating back to the arrival of early European explorers and settlers. The Jewish community in Indonesia is unique and rarely discussed in the context of the country's religious plurality. Despite their relatively small numbers compared to the majority religion, their existence brings important perspectives on assimilation and identity dynamics. This research fills a knowledge gap by investigating the specific dynamics of the Jewish community in the context of assimilation and identity, expanding the understanding of the history of antisemitism and representation as well as Jewish national loyalties and identity in Indonesia. Through qualitative methods and a case study approach, data was collected through in-depth interviews and document analysis to capture the historical perspectives and adaptations of the community. The results show that the Jewish community, although small, has successfully assimilated while maintaining their religious and cultural identity in a social environment dominated by other religions. This research provides new insights into the study of religious plurality, particularly in the context of Muslim-majority Indonesia. It illustrates how assimilation and identity preservation can occur simultaneously, offering a more complex and dynamic perspective than previously recognized. The findings also emphasize the importance of interfaith education and interreligious dialogue as factors that influence the ability of religious minorities to maintain their identities. The results of this study have significant implications for the understanding of religious diversity in Indonesia and how small communities can contribute to the national discourse. The theoretical benefits of the findings enrich the study of religious minority dynamics in plural societies, highlighting that flexibility and adaptation are important aspects in the survival of religious and cultural identities. Practically, the findings can inform the development of more inclusive policies that protect the rights of religious and faith minorities in Indonesia.